2007
DOI: 10.1016/j.jnucmat.2007.03.226
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monte-Carlo modeling of hydrogen isotope reactive–diffusive transport in porous graphite

Abstract: Deuterium and tritium will be the fuel used in a fusion reactor in equal mixtures.It is important to study the recycling and mixing of these isotopes of hydrogen in graphite from several points of view: (i) impact on the ratio of deuterium to tritium in a reactor, (ii) continued use of graphite as a first wall and divertor material, (iii) reaction with carbon atoms and the transport of hydrocarbons will provide insight into chemical erosion. Dynamic Monte-Carlo techniques are used to study the reactivediffusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In the absence of incoming energetic ions, the samples which are 'virgin' (having very less damage), molecules are indeed formed locally at the end of the ion range. Structural dependence of re-emission was also observed by the present authors in previous simulations [9].…”
Section: Experimental Observations By Chiu Et Alsupporting
confidence: 89%
See 2 more Smart Citations
“…In the absence of incoming energetic ions, the samples which are 'virgin' (having very less damage), molecules are indeed formed locally at the end of the ion range. Structural dependence of re-emission was also observed by the present authors in previous simulations [9].…”
Section: Experimental Observations By Chiu Et Alsupporting
confidence: 89%
“…A 3D multi-scale model has been developed to model the hydrogen isotope reactivediffusive transport in porous graphite [8,9]. The two-region model developed by Haasz et al [10] has been implemented distinguishing the atomic and molecular transport processes within the bulk and surface region on the graphite crystallites.…”
Section: Description Of the 3d Kmc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal geometry plays a major role in retention and release, so we will first keep the internal structure the same in all the cases. The effect of void fraction and void size was studied [33], and we have also shown that even the orientation of the voids affects the hydrogen release (this is to be published). For a systematic study, we take a sample with cubic voids, neglecting here the further dependence on the voids.…”
Section: Resultsmentioning
confidence: 83%
“…The input data used include diffusivity, trap sites, etc. and are shown in Table 1 and Table 2, where most of these were used in MD or KMC simulations [14,15,16,25] and gleaned from either experiments (E D , E HD or an educated guess was used (like ω o corresponds to typical phonon frequency [19]). The backscattering rate R is from [27].…”
Section: Hydrogen Isotope Retention In Porous Materialsmentioning
confidence: 99%